Pengembangan Sistem Manajemen Kepegawaian berbasis Web (Studi Kasus Universitas PGRI Madiun) - Elkaf Fahrezi Soebianto Putra; Achmad Arwan; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The administrative process of the University of PGRI Madiun staffing is everything related to the administrative management of the employees of the University of PGRI Madiun (UNIPMA). Matters relating to the administration process of UNIPMA include the appointment of permanent lecturers, promotion of functional lecturers, promotion of employees, inpassing equalization of lecturers, lecturer certification, and dismissal of employees. Some problems are less effective and efficient in the administrative procedures or procedures of the UNIPMA staffing system because the staffing administration process is still carried out manually and conventionally. The length of the procedure, starting from the employee submitting the file, checking the completeness of the file, to waiting for approval from the officials concerned requires a short time. Such conditions will certainly take a lot of time and energy in every time administrative staffing. Also, sometimes the official concerned cannot attend due to having busy outside the campus. In this study a staffing system was developed which is expected to be able to handle the administrative problems of UNIPMA employees. The development of this system uses a waterfall development process model. The stages carried out in this research are problem identification, literature study, engineering requirements, design, implementation, testing, and drawing conclusions and suggestions. This study adopts the evolutionary prototyping model at the requirements engineering stage. This system has been tested by unit testing, integration testing, and validation testing. Unit tests produce valid status in six test cases, integration testing produces valid status in three test cases, and validation testing produces valid status in 102 test cases.